Effect of bovine somatotropin on production parameters in cows* - BHERE, S K; DESHMUKH, B T; NAGVEKAR, A S; TALVELKAR, B A (The Indian Journal of Animal Sciences, 2013)
Apparently healthy multiparous lactating crossbred cows (24) were used for this study. Based on milk production and parity, they were randomly allocated to 4 treatment groups. The 4 treatments were control and 3 dose rates of250 mg, 350’ mg, and 500 mg sometribove zinc suspension in sustained release preparation. Cows in control group received placebo injections of normal saline. Treatments were initiated at 72.79 Â± 2.51 days postpartum and continued for 140 days. The injections were given subcutaneously on left or right side. at every 14 days for 10 injection cycles. The cows were milked by hand milking 2 times a day. The average increases in milk yields relative to cows in control group were 21.960/0, 20.57% and 17.26% in 250 mg, 350 mg, and 500 mg groups respectively. The average increases in milk yield at 4%.FCM over the cows in control group were 24.26% in 250 mg and 350 mg groups and 21.03% in 500 mg group, however, milk composition was not affected. Dry-matter intake remained almost the similar in control and treated cows but a feed efficiency was apparently better in treated cows. The animals maintained good health throughout and treated group registered a gain in body weight. The increase in milk production, observed in this study, could be due to partitioning of nutrients towards the mammary gland for milk synthesis and away from use by body tissues.